Unpacking the Impact of Writing Feedback Perception on Self-Regulated Writing Ability: The Role of Writing Self-Efficacy and Self-Regulated Learning Strategies - Soonhee Hwang (Behavioral Sciences)
Writing is a goal-oriented cognitive activity that requires metacognition and is essential for learners across all academic levels. However, many students struggle with writing skills, which can negatively affect their academic success and future opportunities. This study aimed to analyze factors influencing undergraduates’ writing achievement and to explore the relationships among writing feedback perception, writing self-efficacy, self-regulated learning strategies, and self-regulated writing ability. The study was conducted in two parts: Phase 1 examined the factors affecting the writing achievement of 196 undergraduates, while Phase 2 explored the mediating role of writing self-efficacy and self-regulated learning strategies in the relationship between the writing feedback perception and self-regulated writing ability of 306 undergraduates in Korea. Data were analyzed using Pearson’s correlation, regression, and multiple mediation analyses. Findings from Phase 1 showed that self-regulated learning strategies and self-regulated writing ability predicted writing achievement, while writing feedback perception and writing self-efficacy did not. In Phase 2, three key results emerged. First, writing feedback perception was a significant predictor of writing self-efficacy and self-regulated learning strategies. Second, writing feedback perception, writing self-efficacy, and self-regulated learning strategies significantly predicted self-regulated writing ability. Third, writing self-efficacy and self-regulated learning strategies mediated the relationship between writing feedback perception and self-regulated writing ability. The findings contribute to a deeper understanding of the mechanisms underlying undergraduates’ writing achievement by emphasizing the indirect effects of writing feedback perception through writing self-efficacy and self-regulated learning strategies. The results underscore the role of fostering writing self-efficacy and equipping learners with effective self-regulated learning strategies to enhance writing skills. Additionally, the study highlights the value of well-designed writing feedback as a foundational element for cultivating students’ confidence and autonomy in their writing practices.